2021
DOI: 10.20944/preprints202104.0600.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Characteristics of Carnivore Protoparvovirus 1 With High Sequence Similarity Between Wild and Domestic Carnivores in Taiwan

Abstract: Carnivore protoparvovirus 1 (CPPV-1) is a DNA virus causing gastrointestinal disease and immunosuppression in various terrestrial carnivores. Domestic dogs and cats are considered the primary CPPV-1 reservoirs. The habitat overlaps of wild carnivores and free-roaming dogs increases the threat of CPPV-1 transmission between them. This study explored the CPPV-1 distribution among wild carnivores through PCR screening and compared the DNA sequences of the partial capsid protein (VP2) between wild and domestic car… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Although FPV has existed for over 100 years and remains without visible changes today, CPV has undergone significant antigenic changes that arose in dog populations in the 1970s, resulting in sub-antigenic variants. These are CPV-2a, CPV-2b, and finally CPV-2c, respectively (Balboni et al 2021;Chang and Chen 2021). The host range of CPV includes nearly all species of wild and domestic carnivores but is more commonly identified in domestic dogs (Canis lupus familyis) and cats (Felis silvestris catus).…”
Section: Parvovirus Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although FPV has existed for over 100 years and remains without visible changes today, CPV has undergone significant antigenic changes that arose in dog populations in the 1970s, resulting in sub-antigenic variants. These are CPV-2a, CPV-2b, and finally CPV-2c, respectively (Balboni et al 2021;Chang and Chen 2021). The host range of CPV includes nearly all species of wild and domestic carnivores but is more commonly identified in domestic dogs (Canis lupus familyis) and cats (Felis silvestris catus).…”
Section: Parvovirus Infectionmentioning
confidence: 99%
“…Results of these studies showed that wild and domestic carnivores share the closely related or same parvoviruses. (Calatayud et al 2020;Balboni et al 2021;Chang and Chen 2021). The pathological and epidemiological features of Carnivore parvoviruses are not reported.…”
Section: Parvovirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most CPV-2 variants are characterized by a glycine residue at position 300 of the VP2 sequence, which has been demonstrated to be necessary for the infection of canine and felid species (Allison et al, 2016;Voorhees et al, 2019). The findings of numerous studies have indicated that the CPV-2a variant can infect wild civet cats (Paradoxurus musangus ) (Mendenhall et al, 2016), red pandas (Ailurus fulgens ) (Qin, Loeffler, Li, Tian, & Wei, 2007), masked palm civets (Paguma larvata ), and Chinese ferret badgers (Melogale moschata ) (Chang & Chen, 2021) in East Asian countries. The CPV-2c variant has also been confirmed to infect masked palm civets and Chinese ferret badgers (Chang & Chen, 2021).…”
Section: Phylogeny and Vp2 Amino Acid Sequence Substitutionsmentioning
confidence: 99%
“…The findings of numerous studies have indicated that the CPV-2a variant can infect wild civet cats (Paradoxurus musangus ) (Mendenhall et al, 2016), red pandas (Ailurus fulgens ) (Qin, Loeffler, Li, Tian, & Wei, 2007), masked palm civets (Paguma larvata ), and Chinese ferret badgers (Melogale moschata ) (Chang & Chen, 2021) in East Asian countries. The CPV-2c variant has also been confirmed to infect masked palm civets and Chinese ferret badgers (Chang & Chen, 2021). Moreover, CPV-2 has been established to be highly prevalent in farmed raccoon dogs and has evolved in only 10 years (Lu et al, 2020).…”
Section: Phylogeny and Vp2 Amino Acid Sequence Substitutionsmentioning
confidence: 99%